Patriarki Domestik Novel Perempuan Berkalung Sorban Karya Abidah El Khalieqy - Kusumawati, Hesty (Universitas Pendidikan Ganesha, 2018)
The symptoms of patriarchy open space controversy due to the emergence of violent men over women at once into the wetlands for the author to dismantle, even readers in order to build awareness of arif in facing the sides of life nuances of patriarchy. Women Berkalung Turbans works Abidah El Khalieqy loaded with patriarchy. This study mengolaborasikan the theory of domination, patriarchy, and violence in the realm of Sociology literature. Writers in its implementation be flexible over existing theories to be more critical and not stuck in one perspective. The results of the analysis showed that the patriarchal Women Berkalung Turbans as follows: 1). the domestic violence directly marked Patriarchal presence of actions, deeds, and the behavior of injure, damage, and destroyed with the intent to legitimize power, and 2). The patriarchal domestic violence indirectly signaled the presence of dirty sayings, not worthy, and deviate from the norm with the aim of influencing the mindset and psychic, so woke up the image that men are more important than women.